2012
DOI: 10.1016/b978-0-12-386503-8.00005-3
|View full text |Cite
|
Sign up to set email alerts
|

A Roundabout Way to Cancer

Abstract: The Slit family of secreted proteins and their transmembrane receptor, Robo, were originally identified in the nervous system where they function as axon guidance cues and branching factors during development. Since their discovery, a great number of additional roles have been attributed to Slit/Robo signaling, including regulating the critical processes of cell proliferation and cell motility in a variety of cell and tissue types. These processes are often deregulated during cancer progression, allowing tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 152 publications
(285 reference statements)
1
108
0
Order By: Relevance
“…These observations suggest that SLIT2-ROBO signaling occurs physiologically in the pancreas, which is in line with the reported chemorepellent function of SLIT2 in epithelial differentiation and ductal morphogenesis during breast, lung, colon, and kidney development (20)(21)(22). In turn, loss of SLIT2 resulted in deregulated morphogenesis and aberrant epithelial growth in lung and breast cancer (10), which agrees with the current observation of reduced SLIT2 mRNA expression in PDAC. Moreover, the concept of SLIT2 as a tumor suppressor in PDAC is supported by the frequent loss of SLIT2 expression in PDAC cell lines (33,34).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These observations suggest that SLIT2-ROBO signaling occurs physiologically in the pancreas, which is in line with the reported chemorepellent function of SLIT2 in epithelial differentiation and ductal morphogenesis during breast, lung, colon, and kidney development (20)(21)(22). In turn, loss of SLIT2 resulted in deregulated morphogenesis and aberrant epithelial growth in lung and breast cancer (10), which agrees with the current observation of reduced SLIT2 mRNA expression in PDAC. Moreover, the concept of SLIT2 as a tumor suppressor in PDAC is supported by the frequent loss of SLIT2 expression in PDAC cell lines (33,34).…”
Section: Discussionsupporting
confidence: 91%
“…By now, three mammalian SLIT homologues (SLIT1-3) have been characterized. The activity of secreted SLIT ligands is mediated through interaction with Robos, which are single-pass transmembrane receptors belonging to the immunoglobulin superfamily of cell adhesion molecules (8)(9)(10). Originally characterized as repulsive axon guidance cues in midline crossing of commissural axons during neural development (11,12), subsequent genetic studies confirmed SLITs and ROBOs as chemorepellent cues controlling axon guidance and branching (13), migration of neurons and glia (14,15), and navigation of neural crest cells during neurogenesis (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations